Distribution and population structure of the fish Cyphocharax gilbert (Characiformes: Curimatidae) in the Lower Paraíba do Sul River, Brazil - Menezes, M.S.; Caramaschi, E.P. (Revista de Biología Tropical, 2007)
The distribution and population structure of Cyphocharax gilbert in four areas of the lower Paraíba do Sul River and its major tributaries (22°S, 43°W) were analyzed between March 1989 and February 1990. The species was common throughout the area, preferring major rivers with high turbidity and sand-mud substrates and range of length and size of specimens found varied depending on the particular characteristics of the site. A predominance of females was found in only area. Nevertheless, in all areas the bimonthly analysis showed preponderance of one of the sexes in periods before or after spawning. Males prevailed in shorter length classes and females in longer ones. There was a prevalence of young in one area that probably was used as a growth and feeding zone.